Immigration and national security - Ting, Jan C. (2006)
Opines that the greatest threat to U.S. homeland security comes from illegals who enter the country through its porous borders in order to attack. Suggests that legal immigration itself needs reform, particularly the visa-waiver program and the rules governing dual citizenship, which pose further security challenges.